The Combination of Mulberry Extracts and Silk Amino Acids Alleviated High Fat Diet-Induced Nonalcoholic Hepatic Steatosis by Improving Hepatic Insulin Signaling and Normalizing Gut Microbiome Dysbiosis in Rats. (30th May 2019) - Park, Sunmin; Zhang, Ting; Qiu, Jing Yi; Wu, Xuangao
Abstract : Mulberry water extracts (MB) and silk amino acids (SA) are reported to improve oxidative stress and inflammation, respectively. We hypothesized whether the mixture of mulberry water extracts and silk amino acids can alleviate nonalcoholic fatty liver disease (NAFLD) induced by high fat diets. Male Sprague Dawley rats were orally provided with high fat diets containing different ratios of MB and SA (1:3, MS1:3, or 1:5, MS1:5) or cellulose (the disease-control) for 12 weeks. Rats had 200 or 600 mg/kg bw of MS1:3 and MS1:5 (MS1:3-L, MS1:3-H; MS1:5-L, and MS1:5-H). Rats in the normal-control group were fed the 20% fat diet with cellulose. Disease-control rats exhibited much greater triglyceride (TG) deposition in the liver than the normal-control rats along with increased body weight gain, visceral fat mass, serum concentrations of cholesterol, triglyceride and nonesterified fatty acid (NEFA), and insulin resistance. Disease-control rats also had liver damage with increased oxidative stress and inflammation compared to the normal-control rats. MS1:3-H and MS1:5-H were found to have greater hepatic glycogen accumulation and decreased hepatic TG, insulin resistance, and dyslipidemia, with MS1:5-H being similar to the normal-control. MS1:3-H alleviated oxidative stress with lower hepatic lipid peroxide compared to MS1:5-H whereas MS1:5-H ameliorated inflammation and hepatocyte damage better than MS1:3-H. Both MS1:3-H and MS1:5-H potentiated hepatic insulin signaling (pAkt ⟶ pACC) and reduced the mRNA expression of TG synthesis genes mRNA (FAS and SREBP-1c). In the gut microbiome MS1:3-H elevated the ratio of Bacteroidales to Clostridiales in the cecum better than MS1:5-H but MS1:5-H reduced the proinflammatory Turicibacterales . In conclusion, both MS1:3-H and MS1:5-H prevented liver damage induced by high fat diets, mainly by suppressing oxidative stress and inflammation, respectively. MS1:3 and MS1:5 might be used as therapeutic agent for NAFLD.